(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The cognitive network is the main research area for the forthcoming wireless technology and is most effectual solution to stable the spectrum insufficiency and recover the utilization of the spectrum. However, there are various open challenges and random atmosphere of CRNs, where unlicensed users which are secondary users can feel free to use the channels that are not occupied by the licensed users which are primary users. So this paper shows that the enhancement of the security using signal and multiple relay selections to increase the security and reliability in cognitive radio networks. In this paper the hybrid Decode amplify and forward (DAF) approach is used by using Huffman coding. The whole arrangement is done in MATLAB environment. It is noticed form the result and discussions that our proposed approach is able to achieve less bit error rate and high capacity to reduce the vulnerabilities in cognitive radio networks (CRN).